Why are there so many species of herbivorous insects in tropical rainforests? - Novotny, Vojtech; Drozd, Pavel; Miller, Scott E; Kulfan, Miroslav; Janda, Milan; Basset, Yves; Weiblen, George D (Science (New York, N.Y.), 2006)
Despite recent progress in understanding mechanisms of tree species coexistence in tropical forests, a simple explanation for the even more extensive diversity of insects feeding on these plants has been missing. We compared folivorous insects from temperate and tropical trees to test the hypothesis that herbivore species coexistence in more diverse communities could reflect narrow host specificity relative to less diverse communities. Temperate and tropical tree species of comparable phylogenetic distribution supported similar numbers of folivorous insect species, 29.0 +/- 2.2 and 23.5 +/- 1.8 per 100 square meters of foliage, respectively. Host specificity did not differ significantly between community samples, indicating that food resources are not more finely partitioned among folivorous insects in tropical than in temperate forests. These findings suggest that the latitudinal gradient in insect species richness could be a direct function of plant diversity, which increased sevenfold from our temperate to tropical study sites.
Keywords: Biodiversity; Lepidoptera; brouci; Papua New Guinea; stromy; Insecta; stravovací zvyklosti; Papua Nová Guinea; Slovakia; Slovenská republika; fylogeneze; Česká republika; tropické klima; Phylogeny; Trees; biodiverzita; podnebí; Climate; Population Density; Czech Republic; larva; Animals; hmyz; zvířata; Coleoptera; Larva; Tropical Climate; hustota populace; Feeding Behavior